Revisiting some chalcogenides for thermoelectricity - Maignan, Antoine (Sci Technol Adv Mater, 2012)
Thermoelectric materials that are efficient well above ambient temperature are needed to convert waste-heat into electricity. Many thermoelectric oxides were investigated for this purpose, but their power factor (PF) values were too small (∼10(−4) W m(−1) K(−2)) to yield a satisfactory figure of merit zT. Changing the anions from O(2−) to S(2−) and then to Se(2−) is a way to increase the covalency. In this review, some examples of sulfides (binary Cr–S or derived from layered TiS(2)) and an example of selenides, AgCrSe(2), have been selected to illustrate the characteristic features of their physical properties. The comparison of the only two semiconducting binary chromium sulfides and of a layered AgCrSe(2) selenide shows that the PF values are also in the same order of magnitude as those of transition metal oxides. In contrast, the PF values of the layered sulfides TiS(2) and Cu(0.1)TiS(2) are higher, reaching ∼10(−3) W m(−1) K(−2). Apparently the magnetism related to the Cr–S network is detrimental for the PF when compared to the d(0) character of the Ti(4+) based sulfides. Finally, the very low PF in AgCrSe(2) (PF = 2.25 × 10(−4) W m(1) K(−2) at 700 K) is compensated by a very low thermal conductivity (κ = 0.2 W m(−1) K(−1) from the measured C(p)) leading to the highest zT value among the reviewed compounds (zT(700K) = 0.8). The existence of a glassy-like state for the Ag(+) cations above 475 K is believed to be responsible for this result. This result demonstrates that the phonon engineering in open frameworks is a very interesting way to generate efficient thermoelectric materials.